Occurrence and impact of negative behaviour, including domestic violence and abuse, in men attending UK primary care health clinics: a cross-sectional survey. Issue 5 (19th May 2015) - Hester, M; Ferrari, G; Jones, S K; Williamson, E; Bacchus, L J; Peters, T J; Feder, G
Abstract : Objective: To measure the experience and perpetration of negative behaviour, including domestic violence and abuse (DVA), and investigate its associations with health conditions and behaviours in men attending general practice. Design: Cross-sectional questionnaire-based study conducted between September 2010 and June 2011. Setting: 16 general practices in the south west of England. Participants: Male patients aged 18 or older, attending alone, who could read and write English. A total of 1403 of eligible patients (58%) participated in the survey and 1368 (56%) completed the questions relevant to this paper. 97% of respondents reported they were heterosexual. Main outcome measures: Lifetime occurrence of negative behaviour consistent with DVA, perceived health impact of negative behaviours, associations with anxiety and depression symptoms, and cannabis use in the past 12 months and binge drinking. Results: 22.7% (95% CI 20.2% to 24.9%) of men reported ever experiencing negative behaviour (feeling frightened, physically hurt, forced sex, ask permission) from a partner. All negative behaviours were associated with a twofold to threefold increased odds of anxiety and depression symptoms in men experiencing or perpetrating negative behaviours or both. 34.9% (95% CI 28.7% to 41.7%) of men who reported experiencing negative behaviour from a partner, and 30.8% (95% CI 23.7% to 37.8%) of men who perpetrated negative behaviours said they had been in a domestically violent or abusive relationship. No associations with problematic drinking were found; there was a weak association with cannabis use. Conclusions: DVA is experienced or perpetrated by a large minority of men presenting to general practice, and these men were more likely to have current symptoms of depression and anxiety. Presentation of anxiety or depression to clinicians may be an indicator of male experience or perpetration of DVA victimisation.